Hubungan Distribsi Varietas Tebu Unggul Lokal dengan Penampilan Fisik Tanaman di Daerah Pengembangan Tebu - Soeprapto Soeprapto; Trikuntari Dianpratiwi (Jurnal Dinamika Sosial Ekonomi, 2004)
Paradigm of high yielding local variety of sugarcane had been adopted until 1995 must be understanded by the user that not all of high yielding variety will be hig yielding at all area. Be Estimated that highyielding local variety of sugarcane had been distributed to users had not been satisfactory preference the users so that users plant other varieties. The reserch to study rointion between distribution of high elching local variety of sugarcane and physic performance of sugarcane. Data secunder had been collected from right SF at West Java, Centre of hoa and East Jim (1999-2000) and empiric data from Sumberharjo SF, Pangka SF and Kebon Agung SF. The last three SF are place that activity of technology dissemination demonstrated (plant season 2003-2004). Analysis had been done by compare distribution of varieties with climat appropriate and physic performance and area of varieties had been distributed. The conclusion of the research is distribution of high yielding sugarcane varieties at some SF hatt not been appropriate unith type of climat but physic performance. Keyword: distribution, local sugarcane variety, physic performance